2012
DOI: 10.1002/app.36454
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between viscoelasticity, microstructure, and molecular properties of zein and pennisetin melts

Abstract: Cereals are a large source of biopolymers, where mainly the starch is used for food and feed. A rapidly growing cereal application is the production of biofuel, mainly produced from corn in the US. The starch is fermented to ethanol leaving spent grain rich in cereal proteins as a by‐product. The corn protein zein is currently extracted on a large scale and used in, for example, material applications. Similarly, pennisetin can be extracted from pearl millet, a crop critical for food security in sub‐Saharan Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The main polypeptides in the native proteins were found at around 12, 20, 23, 35, and 43 molecular weights for PP, the bands were observed at 54,43, 40, 20, and 12 for FP, while in SP, main bands were identified at 50, 43, 20, 18, and 12 kDa. The bands identified are in accordance with the results obtained for a protein concentrate of white millet and yellow millet by Mohamed et al 22 The main polypeptide band for all the native protein varieties was found around 20 kDa in the present study (Figure 1), corresponding to the prolamin fraction of proteins, which is in accordance with the results reported by Goḿez-Marti ́nez et al 23 Moreover, the protein bands found below 20 kDa represent the albumin fraction of proteins. 24 Upon nanoreduction due to sonication treatment, the molecular bands were observed in the range 27−10 kDa, which could be due to the breakage of intermolecular hydrogen and hydrophobic bonds that leads to the reduced molecular weights of proteins.…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (S...supporting
confidence: 93%
“…The main polypeptides in the native proteins were found at around 12, 20, 23, 35, and 43 molecular weights for PP, the bands were observed at 54,43, 40, 20, and 12 for FP, while in SP, main bands were identified at 50, 43, 20, 18, and 12 kDa. The bands identified are in accordance with the results obtained for a protein concentrate of white millet and yellow millet by Mohamed et al 22 The main polypeptide band for all the native protein varieties was found around 20 kDa in the present study (Figure 1), corresponding to the prolamin fraction of proteins, which is in accordance with the results reported by Goḿez-Marti ́nez et al 23 Moreover, the protein bands found below 20 kDa represent the albumin fraction of proteins. 24 Upon nanoreduction due to sonication treatment, the molecular bands were observed in the range 27−10 kDa, which could be due to the breakage of intermolecular hydrogen and hydrophobic bonds that leads to the reduced molecular weights of proteins.…”
Section: Sodium Dodecyl Sulfate-polyacrylamide Gel Electrophoresis (S...supporting
confidence: 93%
“…Herein, the process for making bioplastic films or sheets involves generally three steps: The addition of a small polar molecule as plasticizer (glycerol [12][13][14][15][16], urea [17], ethylene glycol [18,19], diethanolamine, triethanolamine [20], mannitol, diglycerol or lipids [21,22]) surrounding the macromolecules, contributing to the breaking of the intramolecular bonds; and self-reorganization of the released biopolymer chains later into a different shape for finally generating a new 3D network stabilized by new artificial intermolecular hydrogen bonds and ionic interactions. The principal consequences of a plasticizer addition are the promoted chains mobility and the decrease of glass transition temperature (Tg) in parallel to the decrease of rigidity and mechanical strength [23,24].…”
Section: Introductionmentioning
confidence: 99%